2018
DOI: 10.1177/1010539518768573
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Exclusive Breastfeeding and Factors Associated With Exclusive Breastfeeding of Children in Trongsa District, Bhutan

Abstract: The World Health Organization estimated that about 800 000 infant deaths could be prevented annually by exclusively breastfeeding infants for the first 6 months of life. This study aimed to examine the prevalence of exclusive breastfeeding and its associated factors. A total of 192 mothers participated. The prevalence of exclusive breastfeeding practice in Trongsa district was 97% at 1 month, declining to 58% at 6 months. Mothers who returned to formal work were less likely to exclusively breastfeed than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
5
1
1
Order By: Relevance
“…e present study found slightly less than three-fourths of the babies were exclusively breast fed (EBF) for complete 6 months of age. However, several other studies conducted in different [24], and other studies conducted in Nepal [25][26][27], south India [28], Trongsa District, Bhutan [29], northwest Ethiopia [30], and Jimma town, southwest Ethiopia [31] reported a lower proportion of the babies were exclusively breast fed for 6 months than the present study. In contrast to this study, another study conducted in Chepang communities of Makawanpur district, Nepal [32], and Northwest Ethiopia [33] found that higher proportion of the babies were exclusive breast fed until 6 months.…”
Section: Discussioncontrasting
confidence: 88%
“…e present study found slightly less than three-fourths of the babies were exclusively breast fed (EBF) for complete 6 months of age. However, several other studies conducted in different [24], and other studies conducted in Nepal [25][26][27], south India [28], Trongsa District, Bhutan [29], northwest Ethiopia [30], and Jimma town, southwest Ethiopia [31] reported a lower proportion of the babies were exclusively breast fed for 6 months than the present study. In contrast to this study, another study conducted in Chepang communities of Makawanpur district, Nepal [32], and Northwest Ethiopia [33] found that higher proportion of the babies were exclusive breast fed until 6 months.…”
Section: Discussioncontrasting
confidence: 88%
“…Bhutan is in an advanced stage to launch the “accelerating mother and child health care—1000 golden day plus allowance.” This conditional cash transfer mechanism is expected to boost achievements in institutional delivery and other related indicators such as exclusive breastfeeding. 17 However, it may not address the issue of inequity as per Indonesian experience. 18…”
Section: Discussionmentioning
confidence: 99%
“…This conditional cash transfer mechanism is expected to boost achievements in institutional delivery and other related indicators such as exclusive breastfeeding. 17 However, it may not address the issue of inequity as per Indonesian experience. 18 Following are some of the recommendations to overcome the barriers to institutional deliveries highlighted by this study: (1) Simple needs-based interventions such as improving the heating system and providing warm clothes to be used after being discharged from the health centers coupled with awareness on the importance of an institutional delivery could encourage women in cold places to come to health centers for their delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluated exclusive breastfeeding for 5 months or more in Sri-Lanka to be 81.3% the difference may be attributed to the duration of evaluation of breastfeeding [11]. Also in Bhutan which was ranked the lowest country in the South Asian region for exclusive breastfeeding according to the WHO, reported the prevalence of exclusive breastfeeding practice decreased with age from 97% at 1 month to 58% for 5-to 6-month-old infants [12]. Table 2 shows that the studied lactating mothers don't use syringe and fingers, tube and fingers and nipple shield, as regard the most frequently used alternative techniques,tight nipple bottles are used once, till 5 times and more than 5 times in (6.7%, 22.5% & 27.0%) respectively, followed by Syringe which are used once, till 5 times and more than 5 times in (11.4%, 23.9% & 9.1%) respectively, wide nipple bottles are used in only 18%, followed by cups and feeding tubes (7.9% & 5.7%) respectively.…”
Section: Discussionmentioning
confidence: 99%